CEO Gender And Earnings Management - Na, Kyunga; Hong, Jooyeon (Journal of Applied Business Research, 2017)
Using the female CEO and male CEO groups over a 14-year (1992–2013) period, we find that the male CEOs use aggressive discretionary accruals and real activities operations in order to report small positive earnings or small earnings increases whereas the earnings management using real activities operation of suspect firms disappear in the female CEO group.
Keywords: CEO Gender; Earnings Management; Accruals Earnings Management; Real Activities Management